Polymer latex for improving air tightness of concrete and preparation method thereof

By designing polymer latex with multi-layer structures, the airtightness and interface bonding strength of concrete are improved, and the problem of polymer incorporation in the prior art affects the strength of concrete is solved, and the airtightness of concrete is significantly improved at low dosage Sexual effect.

CN119241780APending Publication Date: 2025-01-03RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411277576.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The research on concrete modification of existing polymers mostly focuses on matrix toughening and water permeability improvement, and pays less attention to the improvement of airtightness. Especially in low vacuum environments, polymers are easily affected when incorporated, resulting in Decreased intensity.

Method used

Copolymer polymer latex using hard monomer, soft monomer and functional monomer to improve the interface bonding ability of latex in concrete by designing multi-layer structures and introducing functional groups such as epoxy, carboxyl, hydroxyl, and phosphate groups. and anti-aircraft impact properties, combined with emulsifiers and initiators, polymer latex with high film formation and low doping properties were prepared.

Benefits of technology

At low dosage, the airtightness of concrete is significantly improved, good working performance is maintained, and the interface bonding strength and airflow resistance of concrete are enhanced. It is suitable for low-vacuum pipeline transportation infrastructure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of polymer modified cement-based materials, in particular to polymer latex for improving air tightness of concrete and a preparation method of the polymer latex. According to the polymer latex prepared by the invention, through composition design and optimization of the hard monomer, the soft monomer and the functional monomer, good film forming, bonding and compacting effects of the synthesized latex in concrete are realized, and strong polar functional groups such as epoxy groups, carboxyl groups, hydroxyl groups and phosphate groups are introduced into the molecular structure of the latex; a strong electrostatic adsorption effect can be formed with a cement hydration product, the interface bonding capacity of a latex film in concrete is improved, and the compaction effect is better; a branched chain structure is introduced into a latex molecular structure, so that intermolecular slippage during deformation of a latex film can be increased, the loss factor of the latex film is controlled, and the effect of resisting airflow impact is improved; a polyether unit on a side chain can provide a certain water reducing function, so that the workability of a cement-based material is easier to adjust when the latex is used in the cement-based material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer modified cement-based materials, and in particular to a polymer latex for improving the air tightness of concrete and a preparation method thereof. Background Art

[0002] In order to achieve a higher economical operating speed, on the basis of using suspension technology to reduce vehicle-rail friction and vibration, building a low vacuum operating environment to reduce air resistance and noise is an important development direction for future higher-speed rail transportation technology. Among them, improving the air tightness of infrastructure concrete is one of the key technologies for building a low vacuum pipeline transportation system.

[0003] The use of polymers to modify concrete to obtain polymer modified concrete (PCC) can improve the air tightness of concrete materials. Polymer modified concrete is an organic-inorganic composite material formed by adding organic polymer materials dispersed in water or dispersible in water as a medium to a uniformly mixed mixture of cement and aggregate. The role of polymers in concrete can be divided into two categories: physical and chemical. The physical role is mainly manifested in the interweaving of polymers and cement products into a network structure, improving the transition zone structure and pore structure, etc.; the chemical role mainly includes the reaction of polymers with cement hydration products or metal ions in concrete to produce a bridging effect, improving the density and bonding of concrete. In general, polymers can fill microcracks in concrete and allow the polymer film to penetrate the mortar. It can reduce the porosity and fill the pore structure inside the concrete, and has a densifying effect on the concrete. It also has a toughening and modification effect on the concrete. For example, invention patent application CN107473645 B discloses a high-damping concrete based on internal structure design and a preparation method thereof. The concrete is modified using polymer emulsion. The resulting concrete has good energy absorption and dissipation effects, and mechanical properties such as flexural and compressive strength can be controlled within a reasonable range.

[0004] However, the current research on the use of polymers to modify concrete is mostly focused on matrix toughening and water permeability improvement, while there is relatively little research on improving air tightness, especially for the improvement of concrete air tightness in low vacuum environments, which is still a cutting-edge research field. In this regard, there are still some problems to be solved or improved, including the fact that the addition of polymers will affect the working performance of fresh concrete and cause the strength of concrete to decrease. The occurrence of this problem is related to the amount of latex added. If the latex can achieve an effective concrete density improvement effect at a lower dosage, it will be expected to solve the impact on the performance of concrete mixtures and the strength of the hardened body, and enhance the practical application value of the corresponding technology in low vacuum pipeline transportation infrastructure. Summary of the invention

[0005] The object of the present invention is to solve the above problems and provide a polymer latex for improving the air tightness of concrete, and a method for preparing the material.

[0006] The polymer latex is a copolymer of three types of polymerizable monomers: hard monomer, soft monomer and functional monomer. The hard monomer is an aromatic vinyl compound. The soft monomer is one or more of butyl acrylate, pentyl acrylate, hexyl acrylate, lauryl acrylate, butyl methacrylate, pentyl methacrylate and hexyl methacrylate. The hard monomer is one or more of styrene, allyl benzene, methyl acrylate, acrylonitrile, methyl methacrylate, acrylamide and p-vinylbenzene. The functional monomer is an unsaturated acid ester compound, and its general chemical formula is CH2=CR1-COO-CH(-C X H 2X+1 )-(OCH2CH2) Y -A, In the formula, R1 is any one of hydrogen and methyl; 2≤X≤5, 2≤Y≤4, X and Y are positive integers; A is any one of epoxy, carboxyl, hydroxyl, vinyl or phosphate.

[0007] The polymer latex comprises, by mass, 5 to 20 parts of hard monomers, 15 to 25 parts of soft monomers, 2 to 10 parts of functional monomers, 1 to 5 parts of emulsifiers, and 0.1 to 0.5 parts of initiators in the synthetic raw materials.

[0008] The latex particles of the polymer latex have a multilayer structure of an inner layer, an outer layer and a middle layer, wherein the mass fraction of the hard monomers in the inner layer is greater than 80%, the mass fraction of the functional monomers in the middle layer is greater than 10% and less than 40%, and the mass fraction of the soft monomers in the outer layer is greater than 50%.

[0009] The emulsifier is composed of one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, OP-10, OP-20, OP-30, and Triton x100.

[0010] The water vapor permeability of the latex film prepared from the polymer latex is ≤6g / (m 2 ·d).

[0011] The positive tensile bonding strength of the polymer latex after forming a film on the concrete surface is greater than 0.8 MPa.

[0012] The preparation method of the polymer latex is as follows: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, the outer layer monomers mixed in a certain proportion are added, and the dispersion is continued for 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified dispersion A of the outer layer monomers. The intermediate layer monomers are treated according to the above steps to obtain a pre-emulsified dispersion B.

[0013] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add the inner layer polymerization monomer C mixed in a certain proportion, stir with a stirring paddle at a speed of 350r / min, raise the temperature to 80℃, and then add the initiator solution.

[0014] (3) After the latex turns light blue and thickens, the pre-emulsified dispersions A and B are sequentially dripped into the three-necked flask using a peristaltic pump over a period of 2.5 to 3.5 hours. The initiator solution is added at the same time. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a styrene-acrylic copolymer latex.

[0015] The polymer latex has a synthesis conversion rate higher than 97%, a PDI lower than 0.1, and a zeta potential absolute value greater than 30 mV.

[0016] The positive effects of the styrene acrylic latex for improving the air tightness of low vacuum pipeline transportation infrastructure concrete are: Through the composition design and optimization of hard monomers, soft monomers and functional monomers, the synthesized latex has achieved good film-forming, bonding and compacting effects in concrete: the strong polar functional groups such as epoxy, carboxyl, hydroxyl and phosphate introduced in the molecular structure of the latex can form a strong electrostatic adsorption effect with cement hydration products, increase the interface bonding ability of the latex film in concrete, and achieve better compacting effect; the branched structure introduced in the molecular structure of the latex can increase the intermolecular slippage when the latex film is deformed, control the loss factor of the latex film, and enhance the effect of anti-airflow impact; the copolymer stiffness of the inner layer is relatively large, and the particle shape can be maintained in the cement-based material, which has the effect of densely filling the pores of the cement-based material; the polyether unit on the side chain can provide a certain water-reducing function, so that when the latex is used in the cement-based material, the workability of the cement-based material itself is easier to adjust. The polymer latex prepared by the present invention is cheap and has a simple preparation process. It can significantly improve the air tightness of concrete at a low dosage and has little effect on the working performance of concrete. DETAILED DESCRIPTION

[0017] The present invention is further described in detail below with reference to the embodiments. Example 1

[0018] 1. The relevant preparation parameters of polymer latex are: In the general formula of the functional monomer, X=3, Y=3, and A is an epoxy group; Inner layer hard monomer: styrene, mass fraction 85%; Intermediate layer functional monomer: mass fraction 20%; Outer soft monomer: butyl acrylate, mass fraction 60%; The remaining mass fraction not specified in the specific monomer composition of each layer is composed of the relevant mixed monomers; Emulsifier: mixture of sodium lauryl sulfate and OP-10, 1.5 parts; Initiator: ammonium persulfate, 0.3 parts.

[0019] (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, the outer layer monomers mixed in a certain proportion are added, and the dispersion is continued for 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified dispersion A of the outer layer monomers. The intermediate layer monomers are treated according to the above steps to obtain a pre-emulsified dispersion B.

[0020] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add the inner layer polymerization monomer C mixed in a certain proportion, stir with a stirring paddle at a speed of 350r / min, raise the temperature to 80℃, and then add the initiator solution.

[0021] (3) After the latex turns light blue and thickens, the pre-emulsified dispersions A and B are sequentially dripped into the three-necked flask using a peristaltic pump over a period of 2.5 to 3.5 hours. The initiator solution is added at the same time. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a styrene-acrylic copolymer latex. Example 2

[0022] 1. The relevant preparation parameters of polymer latex are: In the general formula of the functional monomer, X=3, Y=3, and A is an epoxy group; Inner layer hard monomer: styrene, mass fraction 85%; Intermediate layer functional monomer: mass fraction 20%; Outer soft monomer: butyl acrylate, mass fraction 60%; The remaining mass fraction not specified in the specific monomer composition of each layer is composed of the relevant mixed monomers; Emulsifier: mixture of sodium lauryl sulfate and OP-10, 1.5 parts; Initiator: ammonium persulfate, 0.3 parts.

[0023] (II) The preparation steps are the same as those in Example 1. Example 3

[0024] (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0025] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0026] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex. Example 4

[0027] (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a sulfonic acid group, 5 parts; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0028] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0029] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex. Example 5

[0030] (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a phosphate group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0031] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0032] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex. Example 6

[0033] (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=1, Y=1, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0034] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0035] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex. Example 7

[0036] (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=6, Y=10, A is a carboxyl group, 5 parts; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0037] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0038] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex. Example 8

[0039] (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=1, Y=10, A is a carboxyl group, 5 parts; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0040] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0041] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0042] Comparative Example 1: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 14 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0043] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0044] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0045] Comparative Example 2: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 26 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0046] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0047] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0048] Comparative Example 3: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 19 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0049] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0050] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0051] Comparative Example 4: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 3 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0052] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0053] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0054] Comparative Example 5: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 1 part; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0055] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0056] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0057] Comparative Example 6: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 26 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 9 parts; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0058] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0059] Comparative Example 7: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=0, Y=1, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0060] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0061] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0062] Comparative Example 8: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=7, Y=1, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0063] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0064] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0065] Comparative Example 9: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 0 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0066] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0067] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0068] Comparative Example 10: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 0 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0069] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0070] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0071] Comparative Example 11: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 0 parts; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0072] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0073] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0074] Comparative Example 12: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=0, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0075] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0076] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0077] Comparative Example 13: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=11, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0078] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0079] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0080] Comparative Example 14: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y+1 , where X=5, Y=7, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0081] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0082] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0083] Comparative Example 15: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 9000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 9000 r / min to obtain a pre-emulsified solution.

[0084] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0085] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 3 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 4 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0086] Comparative Example 16: (I) The raw materials for polymer latex are calculated by mass fraction: Hard monomer: styrene, 20 parts; Soft monomer: butyl acrylate, 20 parts; Functional monomer: chemical formula is CH2=CH(CH3)-CH(-C X H 2X+1 )-C Y H 2Y -A, wherein X=5, Y=7, A is a carboxyl group, 5 copies; Emulsifier: sodium lauryl sulfate, 1.6 parts; Initiator: ammonium persulfate, 0.35 parts; (ii) The preparation steps include: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min. Then, hard monomer, soft monomer and functional monomer are added and dispersed for another 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified solution.

[0087] (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add a small amount of hard monomer, soft monomer and functional monomer, stir with a stirring paddle at a speed of 350 r / min, heat to 80°C, and then add the initiator solution.

[0088] (3) After the latex turns light blue and thickens, the pre-emulsified solution is dripped into the three-necked flask using a peristaltic pump over 2 hours. At the same time, the initiator solution is dripped into the three-necked flask using a syringe pump over 3 hours. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a polymer latex.

[0089] Effect description: project PDI Film forming properties Adhesion strength (MPa) Loss factor (normal temperature) <![CDATA[Gas permeability coefficient (10 -19 m 2 ).]]> Example 1 0.084 good 2.2 2.3 8.5 Example 2 0.065 good 2.4 2.5 8.7 Example 3 0.066 good 2.3 2.1 8.2 Example 4 0.032 good 2.2 2.1 8.3 Example 5 0.045 good 2.1 2.2 8.5 Example 6 0.029 good 2.4 2.3 7.3 Example 7 0.036 good 2.5 2.5 6.9 Example 8 0.034 good 2.4 2.4 8.6 Example 9 0.035 good 2.2 2.1 9.6 Comparative Example 1 0.045 good 1.8 1.5 15.7 Comparative Example 2 0.088 good 1.9 1.6 14.8 Comparative Example 3 0.031 Poor 0.8 1 17.8 Comparative Example 4 0.035 Poor 1.1 1.8 14.7 Comparative Example 5 0.010 Fair 1.5 1.5 14.9 Comparative Example 6 0.055 good 2.4 0.9 15.2 Comparative Example 7 0.023 good 2.4 1.1 14.1 Comparative Example 8 0.029 good 2.1 1.3 19.6 Comparative Example 9 0.031 Poor 1.1 1 19.1 Comparative Example 10 0.089 Poor 1.2 0.8 19.7 Comparative Example 11 0.099 good 2.2 1.5 14.1 Comparative Example 12 0.088 good 2.1 1.3 15.3 Comparative Example 13 0.065 good 2.4 1.5 13.9 Specific characterization method: (1) The PDI (polydispersity index) and Zeta potential of latex were measured by dynamic light scattering method using Zeta potential and nano-laser particle size analyzer; (2) The film-forming property of latex is tested using a minimum film-forming temperature instrument; (3) The tensile bonding strength of the latex-concrete interface is tested in accordance with the provisions of GB50728-2011 Technical Specifications for Safety Appraisal of Engineering Structure Reinforcement Materials; (4) The loss factor of the latex film was tested using DMA (dynamic mechanical analyzer). The specific method is as follows: the prepared latex film was tested using a dynamic mechanical analyzer in uniaxial tensile mode with a test frequency of 1 Hz. During the test, the sample chamber was first cooled to -60°C, kept constant for 3 minutes, and then heated to 60°C at 2°C / min. The data was processed to obtain the loss factor of the latex film in the range of -60~60°C. (5) The gas permeability coefficient of polymer latex modified concrete was measured using a Torrent gas permeability coefficient tester after 50 cycles of normal pressure-low vacuum.

[0090] It can be seen from the results of Example 1 and Comparative Examples 1 and 2 that the mass fraction of the inner layer hard monomer in Comparative Example 1 is lower than the appropriate range, causing the damping temperature range of the latex film to move toward low temperature, its room temperature loss factor to decrease, the damping performance to decrease, and the air tightness of the latex modified concrete to deteriorate after undergoing normal pressure-low vacuum cycle.

[0091] From the results of Example 1 and Comparative Examples 3, 4 and 5, it can be seen that the mass fraction of the outer soft monomer in each comparative example is lower than the appropriate range, resulting in decreased film-forming and bonding properties of the latex film and deterioration of the air tightness of the latex-modified concrete.

[0092] It can be seen from the results of Example 1 and Comparative Examples 6, 7 and 8 that the mass fraction of the functional monomer in the intermediate layer in each comparative example is lower than the appropriate range, resulting in a decrease in its loss factor, a decrease in damping performance, and a deterioration in the air tightness of the latex-modified concrete after undergoing normal pressure-low vacuum cycles.

[0093] From the results of Comparative Examples 9 and 10, it can be seen that the mass fraction of the inner layer soft monomer and the mass fraction of the outer layer soft monomer are not within the appropriate range, resulting in the damping temperature range of the latex film moving to low temperature, the loss factor at room temperature decreasing, and the film forming property deteriorating and the bonding strength decreasing. Among them, the middle layer in Comparative Example 10 did not use a functional unit, and its damping performance was further reduced, and the air tightness of the latex modified concrete was also worse.

[0094] It can be seen from the results of Example 1 and Comparative Examples 11, 12 and 13 that the functional monomer structures in each comparative example do not meet the requirements, the steric hindrance between the molecular chain segments in the latex film is reduced, and the molecular chain segments are not easy to slide, resulting in a decrease in the loss factor, and the modification effect on the middle layer latex is not good, so that its bonding and damping effects in concrete are not significantly improved.

[0095] In summary, the PDI of the styrene acrylic emulsion for concrete toughening of the present invention is lower than 0.1, and the positive tensile bonding strength on the concrete surface is greater than 2MPa; the loss factor of the latex film obtained under normal temperature conditions is greater than or equal to 2; and the air tightness of concrete can be significantly improved at a low dosage.

Claims

1. A polymer latex for improving the air tightness of concrete and a preparation method thereof, characterized in that The polymer latex is a copolymer of three types of polymerizable monomers: hard monomer, soft monomer and functional monomer. The hard monomer is an aromatic vinyl compound. The soft monomer is one or more of butyl acrylate, pentyl acrylate, hexyl acrylate, lauryl acrylate, butyl methacrylate, pentyl methacrylate and hexyl methacrylate. The hard monomer is one or more of styrene, allyl benzene, methyl acrylate, acrylonitrile, methyl methacrylate, acrylamide and p-vinylbenzene. The functional monomer is an unsaturated acid ester compound, and its general chemical formula is CH2=CR1-COO-CH(-C X H 2X+1 )-(OCH2CH2) Y -A, In the formula, R1 is any one of hydrogen and methyl; 2≤X≤5, 2≤Y≤4, X and Y are positive integers; A is any one of an epoxy group, a carboxyl group, a hydroxyl group, a vinyl group or a phosphate group.

2. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The polymer latex comprises, by mass, 5 to 20 parts of hard monomers, 15 to 25 parts of soft monomers, 2 to 10 parts of functional monomers, 1 to 5 parts of emulsifiers, and 0.1 to 0.5 parts of initiators in the synthetic raw materials.

3. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The latex particles of the polymer latex have a multilayer structure of an inner layer, an outer layer and a middle layer, wherein the mass fraction of the hard monomers in the inner layer is greater than 80%, the mass fraction of the functional monomers in the middle layer is greater than 10% and less than 40%, and the mass fraction of the soft monomers in the outer layer is greater than 50%.

4. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The emulsifier is composed of one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, OP-10, OP-20, OP-30, and Triton x100.

5. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The water vapor permeability of the latex film prepared from the polymer latex is ≤6g / (m 2 ·d).

6. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The positive tensile bonding strength of the polymer latex after forming a film on the concrete surface is greater than 0.8 MPa.

7. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The following steps are involved: (1) Deionized water and emulsifier are placed in a beaker, and then dispersed for 2 minutes using a high-speed disperser at a speed of 10,000 r / min, and then the outer layer polymerization monomers mixed in a certain proportion are added, and the dispersion is continued for 10 minutes at a speed of 10,000 r / min to obtain a pre-emulsified dispersion liquid A of the outer layer polymerization monomers; the middle layer polymerization monomers are treated according to the above steps to obtain a pre-emulsified dispersion liquid B; (2) Weigh a small amount of water and emulsifier into a three-necked flask, then add the inner layer polymerization monomer C mixed in a certain proportion, stir with a stirring paddle at a speed of 350r / min, heat to 80°C, and then add the initiator solution; (3) After the latex turns light blue and thickens, the pre-emulsified dispersions A and B are sequentially dripped into the three-necked flask using a peristaltic pump over a period of 2.5 to 3.5 hours. The initiator solution is added at the same time. After the dripping is completed, the mixture is reacted for another hour, cooled, and filtered to obtain a styrene-acrylic copolymer latex.

8. The polymer latex for improving the air tightness of concrete and the preparation method thereof according to claim 1, characterized in that The polymer latex has a synthesis conversion rate higher than 97%, a PDI lower than 0.1, and a zeta potential absolute value greater than 30 mV.

9. Use of the polymer latex for improving the air tightness of concrete according to any one of claims 1 to 8 in cement-based materials.